(untitled) (Ukrainian Journal of Ophthalmology, 2025)
The All-Ukrainian research/practice conference "Topical Issues of Ophthalmology" was organized in Ivano-Frankivsk on October 9-10, 2019. Organizers of this event were SI «The Filatov Institute of Eye Diseases and Tissue Therapy of NAMS of Ukraine», SO «Ukrainian Society of Ophthalmologists», Ivano-Frankivsk Regional Clinical Hospital, Ivano-Frankivsk National Medical University with the support of the National Academy of Medical Sciences of Ukraine and the Ministry of Healthcare of Ukraine. This huge event in the sphere of health care included up-to-date research and practice program: 9 sessions, training event «The Filatov school» – simulation training «Puzzles in Uveitis» and a meeting of electronic posters. More than 52 Ukrainian and foreign experts presented innovative solutions, inventions, improvement in ophthalmology.